Poor physical fitness is independently associated with mild cognitive impairment in elderly Koreans - SH Lee; JH Han; YY Jin; lH Lee; HR Hong; HS Kang (Termedia Publishing House, 2016)
The purpose of this study was to investigate the association between physical fitness and mild cognitive impairment (MCI) in elderly Koreans. This was a cross-sectional study that involved I34 men and 299 women aged 65 to 88 years. Six senior fitness tests were used as independent variables: 30 s chair stand for lower body strength, arm curl for upper body strength, chair-sit-and-reach for lower body flexibility, back scratch for upper body flexibility, 8-ft up-and-go for agility/dynamic balance, and 2-min walk for aerobic endurance. Global cognitive function was assessed using the Korean version of the Mini-Mental State Examination (MMSE). Potential covariates such as age, education levels, blood lipids, and insulin resistance (IR) markers were also assessed. Compared to individuals without MMSE-based MCI, individuals with MMSE-based MCI had poor physical fitness based on the senior fitness test (SFT). There were significant positive trends observed for education level (p=0.00I) and MMSE score (p<0.001) across incremental levels of physical fitness in this study population. Individuals with moderate (0R=0.34l, p=0.006) and high (0R=0.27l, p=0.007) physical ﬁtness based on a composite score of the SFT measures were less likely to have MMSE-based MCI than individuals with low physical ﬁtness (referent, 0R=I). The strength of the association between moderate (0R=O.377, p=0.038) or high (OR=O.282, p=0.050) physical fitness and MMSE-based MCI was somewhat attenuated but remained statistically significant even after adjustment for the measured compounding factors. We found that poor physical fitness was independently associated with MMSE-based MCI in elderly Koreans.